Iron oxide synergistic vacuum carbothermal extraction of zinc from zinc sulfide - Ma, Hongzhou; Dang, Yubo; Wang, Yaoning; Zeng, Jinyang; Zhang, Xing; Guan, Minghua; Zhao, Xiaojun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
To reduce the problems of large pollutant emissions and long process flow in the process of extracting zinc from zinc sulfide ore, the technical idea of iron oxide combined with vacuum carbothermal reduction to extract zinc from zinc sulfide ore is proposed. The source of iron oxide is metal smelting slag with high iron content. In vacuo, iron oxide is reduced to metallic iron by carbon. Iron replaces zinc sulfide to form zinc vapor, and zinc vapor is condensed to obtain metallic zinc. In this paper, zinc in zinc sulfide was extracted under vacuum conditions with iron powder, pure iron oxide powder, and iron oxide in roasting cyanide tailings as iron sources. The effects of reduction temperature and holding time on zinc volatilization rate were studied. The results show that when nFe : nZn = 1.1 : 1, 1000 °C, the initial pressure in the furnace is 10 Pa, iron powder, pure iron oxide powder, and iron oxide in roasting cyanide tailings can make the zinc volatilization rate in zinc sulfide reach more than 99 %. Different iron sources can react with the sulfur of zinc sulfide to form FeS, and no sulfur-containing gas is generated in the process of zinc extraction.
Keywords: vacuum carbothermal reduction; iron oxide; replacement; zinc sulfide; iron